Maturity modelling integrated with apatite fission-track dating: Implications for the thermal history of the Mid-Polish Trough (Poland) - Resak, Marta; Glasmacher, Ulrich A.; Narkiewicz, M.; Littke, R. (Marine and petroleum geology, 2010)
The Mid-Polish Trough (MPT) is situated in the easternmost part of the Central European Basin System (CEBS) and stretches NW-SE across the Polish Basin. It was characterised by pronounced subsidence and thick sediment accumulation between the Permian and the Late Cretaceous. Late Cretaceous-early Paleogene basin inversion led to the formation of the Mid-Polish Swell (MPS). The study area is located within the Pomeranian segment of the MPT/MPS (NW Poland) and experienced up to 7 km Permian-Mesozoic subsidence. PetroMod 1-D modelling was performed on several well-sections in order to study Permian to recent burial-uplift evolution. The modelling was calibrated with new vitrinite reflectance (VRr) data and allowed to constrain the magnitude of uplift and related erosion as well as provided a first overview of the temperature history. The base of the studied Permian-Mesozoic successions attained maximum burial depths of 4800-5400 m before the onset of the inversion, less than in the axial trough area. The thickness of pre- and most probably also syn-inversion Upper Cretaceous deposits is estimated as 300 m. Erosion associated with inversion processes removed between 900 and 1400 m of the Mesozoic sediments, i.e. 1000-1500 m less than in the most inverted central part of the trough. VRr data suggest constant Permian-Mesozoic heat flows corresponding to present-day values (40-45 mW/m2). Apatite fission-track (AFT) ages modelled with the PetroMod module PetroTracks show a good fit with AFT ages directly measured on well samples, and further support the assumption of steady heat flow in the range 40-45 mW/m2. Palaeotemperatures appear to have decreased towards the East European Craton margin, which is compatible with the present day distribution of heat flow. Thermal history modelling shows a relatively simple Permian-Mesozoic heat flow pattern in the Pomeranian segment of the MPT. Such a scenario implies that the present-day heat flow distribution has not changed essentially since Mesozoic times.
Online verfügbar 21. Juni 2009
Der Artikel wurde versehentlich von Verlagsseite aus zuerst in Volume 27, Heft 1, Januar 2010 veröffentlicht, sollte aber als Teil des Special issue "The link between shallow and deep processes in sedimentary basins" veröffentlicht werden
Gesehen am 15.05.2023